A comparative study of abundance and diversity of phytoplankton in Poblacion and Bolusao River in Lawaan, Eastern Samar. - Melecio, Joanna Marie; Casas, Eulito Jr. V. (Joanna Marie Melecio, 2019)
Aside from being a primary producer in the aquatic ecosystem, phytoplankters are important because their population and composition can define water quality and condition (Sekadente et al. 2004). It is, therefore, significant to study the abundance and species diversity of phytoplankton in a certain body of water such as the river. This study aimed to determine physico-chemical parameter of Bolusao Rver and Poblacion River and to evaluate the rivers' phytoplankton abundance and diversity during the months of October-November 2017, January-2018. Phytoplankton samples were collected by horiontal towing and analyed for cell density and species diversity. The highest average cell density obtained in Bolusao River is of 1.6x10 raised to the power of 4 cells/L while in Poblacion it is of 3.4x10 raised to the power of 4 cells/L. Both of these rivers' high cell densities were recorded from February samples. The most dominant genera in Bolusao include Coscinidiscus sp., Chaetoceros sp., and Leptocylindrus sp. In Poblacion River, the most dominant species are Navicula sp., Melosira sp., and Bacillaria sp. Thirty-five (35) phytoplankton families were observed from Bolusao River while 44 families were recorded to be present in Poblacion River. Based on the Shannon-Weiner diversity index values computed, Poblacion River (with H'=3.21) has a more diverse phytoplankton community than Bolusao River (with H'=2.96). In comparing their total average cell densities, the phytoplankton abundance of Poblacion River is significantly higher than Bolusao River.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.